2021
DOI: 10.1136/bmjopen-2021-048698
|View full text |Cite
|
Sign up to set email alerts
|

How is the medical assistance in dying (MAID) process carried out in Nova Scotia, Canada? A qualitative process model flowchart study

Abstract: ObjectivesThe aims of this study are: (1) to create a flowchart process model of how medical assistance in dying (MAID) occurs in Nova Scotia (NS), Canada and (2) to detail how NS healthcare professionals are involved in each stage of MAID. The research questions are: how is the MAID process carried out and which professionals are involved at which points? and which roles and activities do professionals carry out during MAID?DesignQualitative process model flowchart study with semistructured interviews.Setting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 38 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…However, such measures require time and resources that many lack [ 32 , 38 ]. Patients and their families who were cared for by a multidisciplinary team, or those with palliative care backgrounds, had better support than others in previous studies [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, such measures require time and resources that many lack [ 32 , 38 ]. Patients and their families who were cared for by a multidisciplinary team, or those with palliative care backgrounds, had better support than others in previous studies [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 86%
“…This study highlights the importance of implementing strategies for the safety and wellbeing of healthcare providers to ensure equitable access to MAiD. MAiD team members should be provided adequate remuneration, time and resources to safely implement changes in the legislation and to support patients and family members [ 32 , 37 , 39 , 42 , 47 ]. Mandatory end-of-life care for patients and MAiD-related education are required for all healthcare providers to minimize the burden on palliative care and MAiD providers and improve end-of-life care [ 13 , 37 , 48 ].…”
Section: Recommendationsmentioning
confidence: 99%
“…To illustrate, despite medical college policy in provinces such as Ontario, British Columbia and Nova Scotia requiring doctors who are unwilling to provide VAD based on their beliefs to provide an effective referral, information, or transfer of care 34–36 (the Ontario policy being legally upheld as valid in court 37 ), access problems remain. For example, Nova Scotia research has shown a key delay in starting the VAD process is a failure or refusal of unwilling providers to make a referral 14 …”
Section: Discussionmentioning
confidence: 99%
“…For example, Nova Scotia research has shown a key delay in starting the VAD process is a failure or refusal of unwilling providers to make a referral. 14 Finally, while imposing referral or information duties on doctors may address some access issues, some VAD requests may be directed to other health practitioners (such as nurses) who have a conscientious objection. Further, some institutions object to participating in VAD.…”
Section: Repeal Legal Prohibition On Raising Vadmentioning
confidence: 99%
“…Pharmacists' responsibilities in MAiD may encompass medication dispensing, review of medications with the physician or nurse practitioner, postprovision collection of medications and supplies and documentation of legal requirements. 4,5 Although pharmacists' roles have been largely focused on the physical processes for medication handling, there is an emerging recognition that pharmacists' involvement in MAiD is patient-centred. 6,7 There is growing evidence characterizing the experiences of health care professionals involved with MAiD as emotional.…”
Section: Introductionmentioning
confidence: 99%